Traffic-related air pollution - Khreis, Haneen; Nieuwenhuijsen, Mark; Zietsman, Josias; Ramani, Tara (Elsevier, 2020)
And conclusions -- Suggested readings -- Chapter 10: Evidence from toxicological and mechanistic studies -- Abstract -- Background -- Direct actions of vehicle exhaust emissions in biological systems -- TRAP and the lung -- TRAP and the cardiovascular system -- The lung to the peripheral organs -- The systemic effects of TRAP -- Conclusions, considerations, and implications -- Chapter 11: Biomarkers and omics of health effects associated with traffic-related air pollution -- Abstract -- The exposome and environmental pollutants